Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1093/geront/40.6.663
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Dementia in a Statewide Sample of New Nursing Home Admissions Aged 65 and Older

Abstract: This study estimated the prevalence of dementia in 2,285 new admissions age 65+ to a statewide sample of 59 nursing homes in Maryland, 1992-1995. Dementia was ascertained according to DSM-III-R criteria by an expert panel of geriatric psychiatrists, neurologists, and a geriatrician using detailed information collected by trained lay evaluators from residents, family, staff, and medical records. Admissions to Maryland nursing homes are similar to admissions to nursing homes elsewhere in the United States. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
154
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 264 publications
(158 citation statements)
references
References 42 publications
2
154
2
Order By: Relevance
“…A statewide sample of newly admitted residents from 59 Maryland nursing facilities was identified and recruited between 1992 and 1995 using a twostage process, as reported previously (Magaziner et al, 2000). Facilities were randomly selected and recruited to be representative of all nursing homes statewide.…”
Section: Sample Frame and Cohort Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A statewide sample of newly admitted residents from 59 Maryland nursing facilities was identified and recruited between 1992 and 1995 using a twostage process, as reported previously (Magaziner et al, 2000). Facilities were randomly selected and recruited to be representative of all nursing homes statewide.…”
Section: Sample Frame and Cohort Selectionmentioning
confidence: 99%
“…A detailed description of the dementia ascertainment methodology is available elsewhere (Magaziner et al, 1996). In the overall study population (N = 2,285), we designated 48.2% as having dementia (Magaziner et al, 2000).…”
Section: Resident Assessment On Admissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The annual mortality rate in nursing homes varies from 24% to 32% (Dobbs, Hanson, Zimmerman, Williams, & Munn, 2006), and first-year mortality rates hover around 34% . Investigators have found that nearly 50% of the nursing home population has dementia (Magaziner, et al, 2000). Clearly, significant numbers of older adults live and die in nursing homes.…”
Section: Introductionmentioning
confidence: 99%
“…Hospice can positively benefit end-of-life symptom management where about a fourth of adult deaths in the U.S. now occur (Ersek & Wilson, 2003;Hanson, Sengupta, et al, 2005). Almost 50% of nursing home residents have dementia (Magaziner, et al, 2000) and the prevalence of pain or painful conditions is estimated to be between 49% and 83% among residents with dementia (Bjoro & Herr, 2008). This means that of the approximately 800,000 residents in the U.S. who die in nursing homes, over 400,000 have dementia and 650,000 have pain.…”
Section: Introductionmentioning
confidence: 99%